Developing English For Front Office Material for XII Grade Students at SMK N 2 Singaraja - Dewi, Ketut Puspa; Wedhanti, Nyoman Karina; Dewi, Ketut Sintya; Budasi, I Gede (STKIP AGAMA HINDU SINGARAJA, 2021)
The aim of this study is to develop materials for English for front office use by the XI grade students in first semester at SMK N 2 Singaraja. This study is to develop as supplementary materials based on the student’s need analysis using the theory suggested by Hutchinson and Waters (1987). The subjects of this research included one the front office teacher, 40 students of the school and one of the front office staff who worked at Dash Hotel in Seminyak, Bali. Design and development method (D&D) by Richey & Klein (2017) were applied in this study. A questionnaires and a checklist were used as the instruments in collecting the obtained data of the study. Three steps which include: 1) Design (Conducting Needs Analysis), 2) Develop (Developing the Product), and 3) Evaluation (Judging the quality of the product) were past in in the materials development. The findings of this study show that there were 5 topics needed to be developed which include: (1) Handling incoming calls (2) Handling of telephone calls (3) Reservation process (4) Handling individual reservations (5) Handling group reservations to be develop. Each of which will be developed into a units which consist of input, content focus, language focus, and task. The design materials was categories as a very high validity, therefore it is suggested to be used as the supplementary materials for the school.